Evaluation of latex agglutination test and oxacillin resistant screening agar base (ORSAB) medium for the detection of oxacillin resistant coagulase negative Staphylococci (ORCoNS) (Preliminary study) (Medical Journal of Indonesia, 2007)
Coagulase negative Staphylococci (CoNS) are recognized as an important cause of nosocomial infection, especially in neonates and patients with indwelling prosthetic devices. The CoNS resistance rate to oxacillin has been increasing. Therefore, rapid and accurate detection of oxacillin resistance is essential in order to determine the most appropriate antimicrobial therapy. This study aimed to prove that latex agglutination test and oxacillin resistant screening agar base (ORSAB) medium can be used for rapid detection of oxacilllin resistant CoNS (ORCoNS). Latex agglutination test and ORSAB medium compared with the conventional method was conducted in this study toward 30 clinical isolates of CoNS for the detection of ORCoNS. Mc Nemar test was used to analyze the data. The study result revealed that there was no significant difference (P>0.05) in terms of ORCoNS detection between the latex agglutination test and ORSAB medium on the one hand, and the conventional method on the other. It is concluded that latex agglutination test and ORSAB medium can be used for rapid detection of ORCoNS. (Med J Indones 2007; 16:228-32)